Clinical application of controlled aliasing in parallel imaging results in a higher acceleration (CAIPIRINHA)‐volumetric interpolated breathhold (VIBE) sequence for gadoxetic acid‐enhanced liver MR imaging. Issue 5 (4th April 2013) - Yu, Mi Hye; Lee, Jeong Min; Yoon, Jeong‐Hee; Kiefer, Berthold; Han, Joon Koo; Choi, Byung‐Ihn
Abstract : Purpose: To determine whether a controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA) technique can improve the image quality of three‐dimensional (3D), T1‐weighted gradient echo (T1w‐GRE) imaging compared with the use of a standard, parallel acquisition technique (PAT). Materials and Methods: Sixty‐four patients who underwent liver MR on a 3 Tesla (T) scanner, were included in this study. Twenty minutes after the injection of 0.025 mmole/kg of gadoxetic acid, 3D T1w‐GRE imaging (volumetric interpolated breathhold examination [VIBE]) was acquired twice using a generalized autocalibrating partially parallel acquisition (384 × 250 matrix, acceleration factor [AF] of 2) and a CAIPIRINHA (384 × 380 matrix, AF of 4), respectively. Qualitative image analysis was performed for two image sets. Results: CAIPIRINHA‐VIBE showed better hepatic vessel clarity and lesion conspicuity than standard VIBE ( P < 0.05). CAIPIRINHA‐VIBE in the coronal plane also provided better results of motion artifact and liver edge sharpness than the standard VIBE ( P < 0.05). Despite the more apparent PAT artifact on CAIPIRINHA‐VIBE than on standard VIBE ( P < 0.05), CAIPIRINHA‐VIBE showed better overall image quality. Conclusion: The CAIPIRINHA‐VIBE was able to provide a higher spatial resolution, T1‐weighted imaging with better image quality compared with a standard VIBE. J. Magn. Reson. Imaging 2013;38:1020–1026. © 2013 Wiley Periodicals, Inc.